Combining the Real-Time Vial Sharing Strategy with Daily-Rate Charge Mode for Antimicrobial Drugs of Inpatients: An Economical and Practical Method for Patients and Hospitals - Li J; He Y; Lei X; Cao Z; Liao Y; Wang G; Chen Z; Li X; Liu X (Dove Medical Press, 2023)
Jianquan Li, Yongyang He, Xi Lei, Zhongqiang Cao, Yuwei Liao, Guoqiang Wang, Zebin Chen, Xuejuan Li, Xiaoya Liu Department of Pharmacy, Shenzhen Children's Hospital, Shenzhen, Guangdong Province, People's Republic of ChinaCorrespondence: Xiaoya Liu, Department of Pharmacy, Shenzhen Children's Hospital, Shenzhen, 518026, Guangdong Province, People's Republic of China, Tel +86 075583008256, Email liuxy2949@163.comBackground: Antimicrobial agents' wastage is a huge problem, especially for pediatric patients, resulting in excessive drug expenditure and increasing the economic burden on patients' families. Moreover, the cost of disposing of antimicrobial agents' waste and the risk of environmental and occupational exposure also increased. This study aimed to explore the cost-effectiveness of the vial-sharing strategy combined with the daily-rate charge mode for pediatric inpatients to provide a strategy for reducing patients' expenditures, saving medical costs, and reducing drug proportion.Methods: This retrospective study was conducted at Pharmacy Intravenous Admixture Service (PIVAS), Shenzhen Children's Hospital, Guangdong Province, China, in 2022. Data on prescription drugs were collected from the PIVAS system. Ten antimicrobial drugs with a frequency of prescriptions no less than twice once daily were selected, and the drug costs, drug weight, and drug saved were further analyzed according to the combination of real-time vial sharing strategy and daily-rate charge mode. Traditional single vial charge mode without vial sharing was set as a control strategy. The actual expenditure of the hospital was also calculated and analyzed.Results: During 2022, ¥ 4,122,099 (34.4%) was saved for inpatients by applying a vial-sharing strategy on ten antibacterial agents, and more than 46,343,750 mg (24.6%) of drugs were totally saved. The top 5 drugs saved by the real-time vial-sharing strategy were cefoperazone-sulbactam, vancomycin, amoxicillin-sulbactam, ceftazidime, and meropenem. Taken the price into consideration, the top five payment-saved drugs were vancomycin (¥ 1,522,385), meropenem (¥ 1,311,475), cefoperazone-sulbactam (¥ 736,697), imipenem-cilastatin (¥ 406,092), and amoxicillin-sulbactam (¥ 51,394). Moreover, the account balance of the hospital was up to ¥ 426,499.Conclusion: The real-time vial sharing strategy combined with the daily-rate charge mode greatly reduces drug wastage and patients' payments. It may be useful for hospitals with PIVAS to achieve vial-sharing while protecting the best interest of inpatients.Keywords: real-time vial sharing strategy, daily-charge mode, antimicrobial drugs, inpatients, PIVAS